In the Blood or in the Water? Exploring predictors of Welsh language ability among young people - Davies, Rhys; Huxley, Katy; Poole, John (International Journal of Population Data Science, 2025)
Objectives Cymraeg 2050 outlines the Welsh Government’s strategy for the promotion and the facilitation of the use of the Welsh language and seeks to have a million Welsh speakers by 2050. This paper examines the coherence of Welsh language ability as recorded by the Census comparted to other administrative data sets. Methods Progress towards the Cymraeg 2050 target is to be monitored using census of population data. We explore how the Welsh language abilities of children and their parents recorded in the 2011 Census relate to that subsequently recorded within the National Pupil Database for these same children upon them reaching Year 11. We examine both the language medium of schools that they subsequently attend (English, Welsh or Bi-lingual) and their recorded levels of fluency at these schools. Importantly, for those pupils who go on to attend universities in Wales, we also explore whether these students deem themselves to be Welsh speakers. Results Multivariate logistic regression techniques reveal that those young people who came from households whose parents were recorded as Welsh speakers in the 2011 Census were most likely to record themselves as being Welsh speakers upon attending university. This effect is particularly strong when both parents record themselves as Welsh speakers. The recording of their children’s Welsh ability by parents who complete the Census on behalf of their sons and daughters is a poorer predictor of the self-reported Welsh speaking ability of these young people upon entry to university. The analysis suggests that parents may report their children’s Welsh language ability with error. Conclusion Over reliance on Census data in monitoring progress towards Welsh language targets is problematic. Greater use of administrative data should be used to provide a more accurate assessment of the language abilities of children. The importance of intergenerational transmission poses additional challenges for achieving a million Welsh speakers by 2050.